Analisis Karakteristik Psikologi Atlet Atletik di Kabupaten Pati Menuju Porprov 2023 - Pratiwi, Adinda Resta Putri; Rumini, Rumini (Indonesian Journal for Physical Education and Sport, 2023)
Psychology has an important role in athletics because it focuses on individual skills. The aim of this research is to analyze the psychological aspects of athletic athletes in Pati Regency towards PORPROV in 2023. This research uses a survey method with a quantitative descriptive approach, sample in this research, namely athletic athletes in Pati Regency who passed the 2023 PORPROV limit. The results of the research showed that the anxiety control category was "Poor" 7.7%, "Medium" category 38.5%, "High" category 46.2%, and “Very High” category 7.7%. The mental preparation aspect and concentration aspect obtained a percentage in the "Medium" category of 30.8% and the "High" category of 69.2%. For the motivation aspect, the percentage in the "Medium" category was 15.4% and the "High" category was 84.6%. For the team emphasis aspect, the percentage in the "Medium" category was 38.5% and the "High" category was 61.5%. For the confidence aspect, the percentage in the "Medium" category was 30.8%, the "High" category was 61.5%, and the "Very High" category was 7.7%. Based on these results, it can be concluded that the highest psychological aspect is the motivation aspect. Meanwhile, the lowest psychological aspect is anxiety control.